Assessing the Impact of Trump’s Economic Policy Strategies on Economic Reform in Indonesia - Luhuringbudi, Teguh; Putra, Purnama; Masuwd, Mowafg Abrahem; Alsayd, Abdulnasir Dhaw; Alrumayh, Safa Husayn (Institut Agama Islam Negeri Kerinci, 2025)
This study focuses on the economic policy strategies implemented by Trump and their implications for economic reform in Indonesia, while also uncovering the multidimensional and complex interactions between foreign policy and its impact on the domestic economy. The purpose of this study is to understand the influence of Donald Trump's economic decisions on public behavior, as well as their suitability to policies in Indonesia. The data collection method was carried out using a qualitative approach, using literature studies and analysis of the applicable policy context. The data were analyzed through interdisciplinary nuances that include Public Choice Theory, Behavioral Economics, and Sustainable Economic Development, each of which provides thematic-impressive and case-impactful insights into the dynamics of policy and public response. Primary sources used in this study include academic reports, news articles, and analysis from experts in the field of political economy. The research findings prove that economic policies in the US can trigger sentiments and behavioral patterns that directly affect Indonesian society, especially in the context of dissatisfaction with local policies. The conclusion of this analysis boldly asserts that economic reform in Indonesia needs to capitalize on existing psychological and social factors. The novelty of this research is seen in the development of an analytical framework that links foreign economic policy with broader public responses, as well as the importance of public involvement in the decision-making process. Limitations of this research include the lack of specific quantitative data, and further research is recommended to explore the interaction between policies from other countries and their impacts on Indonesian society more holistically, both directly and indirectly.